Former Communist party membership and present-day entrepreneurship in Central and Eastern Europe - Artjoms Ivlevs; Milena Nikolova; Olga Popova (Global Labor Organization (GLO), 2019)
After the collapse of Communism in Central and Eastern Europe, former party members were particularly likely to start businesses and become entrepreneurs. However, it remains unclear whether this entrepreneurial activity was driven by the resources, information and opportunities provided by former party membership or because people with specific individual attributes were more likely to become party members (self-selection). This study is the first to separate the causal effect of former Communist party membership from self-selection. Using individual-level Life in Transition–III survey and instrumental variables analysis, we find that, in Central and Eastern European countries, membership of former Communist party has facilitated business set-up but not business longevity. Our results also suggest evidence of negative self-selection, meaning that people who joined the former ruling party tended have fewer of the traits associated with entrepreneurship such as motivation, risk tolerance, and entrepreneurial spirit. We show that former Communist party membership still matters for business practices, business ethics, and the nature of doing business in transition economies.
Keywords: L26; P20; P31; 330; communism; communist party; elite networks; entrepreneurship; post-socialist countries